Septic Shock: A Genomewide Association Study and Polygenic Risk Score Analysis. (5th August 2020) - D'Urso, Shannon; Rajbhandari, Dorrilyn; Peach, Elizabeth; de Guzman, Erika; Li, Qiang; Medland, Sarah E.; Gordon, Scott D.; Martin, Nicholas G.; Ligthart, Symen; Brown, Matthew A.; Powell, Joseph; et al.
Abstract: Previous genetic association studies have failed to identify loci robustly associated with sepsis, and there have been no published genetic association studies or polygenic risk score analyses of patients with septic shock, despite evidence suggesting genetic factors may be involved. We systematically collected genotype and clinical outcome data in the context of a randomized controlled trial from patients with septic shock to enrich the presence of disease-associated genetic variants. We performed genomewide association studies of susceptibility and mortality in septic shock using 493 patients with septic shock and 2442 population controls, and polygenic risk score analysis to assess genetic overlap between septic shock risk/mortality with clinically relevant traits. One variant, rs9489328, located in AL589740 . 1 noncoding RNA, was significantly associated with septic shock ( p = 1.05 × 10 –10 ); however, it is likely a false-positive. We were unable to replicate variants previously reported to be associated ( p < 1.00 × 10 –6 in previous scans) with susceptibility to and mortality from sepsis. Polygenic risk scores for hematocrit and granulocyte count were negatively associated with 28-day mortality ( p = 3.04 × 10 –3 ; p = 2.29 × 10 –3 ), and scores for C-reactive protein levels were positively associated with susceptibility to septic shock ( p = 1.44 × 10 –3 ). Results suggest that common variants of large effect do not influence septic shock susceptibility, mortality and resolution; however, genetic predispositions to clinically relevant traits are significantly associated with increased susceptibility and mortality in septic individuals.